Response to article by Matthew Wasserman et al. (2018): “Modeling the sustained use of the 13-valent pneumococcal conjugate vaccine compared to switching to the 10-valent vaccine in Mexico” - Jorge A. Gómez; Adriana Guzman Holst; Javier Nieto (Human Vaccines & Immunotherapeutics, 2019)
In a recent article, Wasserman et al. estimated and forecasted the health and economic impact of switching from the 13-valent (PCV-13) to the 10-valent (PHiD-CV) pneumococcal conjugate vaccine in Mexico’s national immunization program. In this response letter, we highlight various methodological inconsistencies and model input considerations that potentially bias the results and further recommendations made by the authors.